Altered Gut Microbiota Associated With Hemorrhage in Chronic Radiation Proctitis - Liu, Liangzhe; Chen, Chaoyun; Liu, Xia; Chen, Bingcheng; Ding, Chen; Liang, Jinjun (Frontiers in Oncology, 2021)
Chronic radiation proctitis (CRP) caused by pelvic cancer radiotherapy adversely affects patient’s quality of life, especially in patients with prolonged hematochezia. However, previous studies of radiation enteropathy mainly focused on acute irradiation hazards, and the detail pathogenesis process and mechanism of prolonged hematochezia associated with radiation-induce toxicity remain unclear. In this study, we characterized the gut microbiota of 32 female CRP patients with or without hematochezia to reveal the alternation of gut microbiota. Differential patterns of dysbiosis were observed. The abundance of Peptostreptococcaceae, Eubacterium and Allisonella were significantly higher in CRP patients with hematochezia, while the compositions of the Lachnospiraceae, Megasphera, Megamonas and Ruminococcaceae were lower in the microbiota of non-hematochezia patients. Functional prediction suggested significant difference in the expression of mineral absorption and the Arachidonic Acid metabolism proteins between hematochezia and non-hematochezia patients, possibly with coadjutant of radiation-induced inflammation. This study provides new insight to the altered composition and function of gut microbiota in patients with hematochezia, implying the potential use of gut microbiota for assessment and treatment of CRP.